Effectiveness of Nutrition Education Based on Smart Booklet Handling Diabetes Mellitus on Blood Glucose Levels and Macronutrient Intake in Prolanis Members in the Working Area of the Turikale Health Center UPT, Maros Regency - Nurul Ilmi Arianti; Siti Uswatun Hasanah; St Masithah; Andi Rahmaniar MB (Universitas Ibn Khaldun Bogor, 2026)
Background: Type II diabetes mellitus (DM) is a chronic metabolic disease characterized by hyperglycemia due to impaired insulin secretion or resistance. Nutrition education plays an important role in regulating diet and controlling blood glucose levels. Objective: This study aims to determine the effect of nutrition education on Blood Glucose Levels (GDS) and macronutrient intake in patients with type II diabetes mellitus. Methods: The study used a quasi experiment design with a non-equivalent control group pretest-posttest design. A total of 30 respondents were divided into two groups: 4-week nutrition education and no education controls. Data was collected through periodic blood glucose checks, and 24-hour food recalls.Results: Nutrition education had no significant effect on blood glucose levels during (p=0.701). However, there was a significant effect on changes in carbohydrate intake (p=0.002), while energy intake (p=0.133), protein (p=0.735), and fat (p=0.066) showed no significant change. Conclusion: Nutrition education does not have a significant effect on reducing blood glucose levels at any time, but it has a significant effect on increasing carbohydrate intake, although it is not optimal for energy, protein, and fat.